Advances in optical imaging for clinical medicine - Iftimia, Nicusor; Brugge, William R.; Hammer, Daniel X. (Hoboken, N.J. : Wiley, 2011)
'This book provides students, teachers, researchers and clinicians with a strong and established source of information on advanced optical technologies that show real promise of being translated to clinical use'--Provided by publisher
(Publisher-supplied data) Chapter 1. Introduction N. Iftimia, W. Brugge, D. Hammer -- Chapter 2. Traditional Imaging Modalities in Clinical Medicine Dr. I. Iftimia, Tufts University School of Medicine, Radiation Oncology Department and Lahey Clinic, Burlington, MA Dr. H. Mower, Tufts University School of Medicine, Radiation Oncology Department and Lahey Clinic, Burlington, MA -- Chapter 3. Current imaging approaches and further imaging needs in clinical medicine: A clinician perspective Authors: (3.1) Gadi Wollstein1 and Joel S. Schuman1,2,3; 1UPMC Eye Center, Eye and Ear Institute, Ophthalmology and Visual Science Research Center, Department of Ophthalmology, University of Pittsburgh School of Medicine, Pittsburgh, PA; 2Department of Bioengineering, Swanson School of Engineering, University of Pittsburgh; 3 Center for the Neural Basis of Cognition, Carnegie Mellon University and University of Pittsburgh. (3.2) Cetin Karaca, Sevdenur Cizginer, and William R. Brugge; Massachusettys General Hospital, Department of Gastroenterology (3.3) Ik-Kyung Jang and Jin-Man Cho; Massachusetts General Hospital, Department of Cardiology (3.4) Peter Dempsey Lahey Clinic, Deprtment of Neurosurgery, Burlington, MA Tufts School of Medicine Chapter 4. Advances in Retinal Imaging Author: Daniel X. Hammer Physical Sciences, Andover, MA Chapter 5: Confocal Microscopy of Skin Cancer Juliana Casagrande Tavoloni Braga, MD, Itay Klaz, MD, Alon Scope, MD, Daniel Gareau, PhD, Milind Rajadhyaksha, PhD and Ashfaq A. Marghoob, MD Dermatology Service, Memorial Sloan-Kettering Cancer Center, New York, NY, USA Chapter 6 High-resolution optical coherence tomography imaging in gastroenterology Melissa J. Suter Ph.D., Brett E. Bouma Ph.D., Guillermo J. Tearney M.D., Ph.D. Harvard Medical School and Wellman Center for Photomedicine Massachusetts General Hospital, Boston MA
Nanotechnology Approaches for Contrast Enhancement in Optical Imaging and Disease Targeted Therapy Dr. N. Iftimia-Physical Sciences, Andover, MA Lara Milane ? Northeastern University, School of Pharmacy, Boston, MA Dr. Amy Oldenburg- University of North Carolina at Chapel Hill Dr. M. Amiji ? Northeastern University, School of Pharmacy, Boston, MA Chapter 17. Molecular probes foryoptical contrast enhancement of gastrointestinal cancers Jonathan W. Hardy, Jonathan T.C. Liu, Anson W. Lowe and Christopher H. Contag Stanford University School of Medicine
Chapter 7. High-resolution confocal endomicroscopy for gastrointestinal cancer detection Jonathan T.C. Liu, Jonathan W. Hardy, and Christopher H. Contag Stanford University School of Medicine Chapter 8: High-resolution Optical Imaging in Interventional Cardiology Thomas J. Kiernan, MD* Bryan P. Yan, MD* Yoshiaki Kawase, MD** Ik-Kyung Jang, MD. PhD* * Cardiology Division, Massachusetts General Hospital, Harvard Medical School, Boston, USA ** Mount Sinai School of Medicine, New York, NY, USA Chapter 9: Fluorescence Lifetime Spectroscopy in Cardio and Neuroimaging Authors: Laura Marcu (University of California Davis, Davis, CA) Javier A. Jo (Texas A&M University, College Station, TX) Pramod Butte (Cedars-Sinai Medical Center ? Los Angeles, CA) Chapter 10 Advanced Optical Methods for Functional Brain Imaging Alessandro Torricelli, Davide Contini, Lorenzo Spinelli, Matteo Caffini, Antonio Pifferi, Rinaldo Cubeddu IIT, CNR-INFM and CNR-IFN, Politecnico di Milano ? Dipartimento di Fisica Piazza Leonardo da Vinci 32, I-20133 Milan, Italy Chapter 11. Advances in Optical Mammography Xavier Intes, PhD1 Fred S. Azar, PhD, MBA2 1Biomedical Engineering Department, Rensselaer Polytechnic Institute, Troy, NY 12180 2 Siemens Corporate Research Inc., Princeton, NJ 08540 Chapter 12. Photoacoustic Tomography Dr. H. Jiang, Dr. Z. Yuan Department of Biomedical Engineering, University of Florida Gainesville, FL Chapter 13. Optical Imaging and Measurement of Angiogenesis Brian S. Sorg, Ph.D. J. Crayton Pruitt Family Department of Biomedical Engineering University of Florida, Gainesville, FL Chapter 14 High-resolution Phase Contrast Optical Coherence Tomography for Functional Biomedical Imaging Dr. Taner Akkin, University of Minnesota Dr. Digant P. DavŬ University of Texas Arlington Chapter 15. Polarization imaging Dr. Mircea Mujat, Physical Sciences, Inc. Chapter 16
Includes bibliographical references and index.
Keywords: Diagnostic Imaging -- trends; Clinical Medicine -- methods; Diagnostic imaging -- Methods; Optical Devices -- trends